CYP2C19 Genotype‐Guided Antiplatelet Therapy and Clinical Outcomes in Patients Undergoing a Neurointerventional Procedure - Kayla R. Tunehag; Ashton F. Pearce; Layna P. Fox; George A. Stouffer; Sten Solander; Craig R. Lee (Clinical and Translational Science)
ABSTRACT In neurovascular settings, including treatment and prevention of ischemic stroke and prevention of thromboembolic complications after percutaneous neurointerventional procedures, dual antiplatelet therapy with a P2Y12 inhibitor and aspirin is the standard of care. Clopidogrel remains the most commonly prescribed P2Y12 inhibitor for neurovascular indications. However, patients carrying CYP2C19 no‐function alleles have diminished capacity for inhibition of platelet reactivity due to reduced formation of clopidogrel's active metabolite. In patients with cardiovascular disease undergoing a percutaneous coronary intervention, CYP2C19 no‐function allele carriers treated with clopidogrel experience a higher risk of major adverse cardiovascular outcomes, and multiple large prospective outcomes studies have shown an improvement in clinical outcomes when antiplatelet therapy selection was guided by CYP2C19 genotype. Similarly, accumulating evidence has associated CYP2C19 no‐function alleles with poor clinical outcomes in clopidogrel‐treated patients in neurovascular settings. However, the utility of implementing a genotype‐guided antiplatelet therapy selection strategy in the setting of neurovascular disease and the clinical outcomes evidence in neurointerventional procedures remains unclear. In this review, we will (1) summarize existing evidence and guideline recommendations related to CYP2C19 genotype‐guided antiplatelet therapy in the setting of neurovascular disease, (2) evaluate and synthesize the existing evidence on the relationship of clinical outcomes to CYP2C19 genotype and clopidogrel treatment in patients undergoing a percutaneous neurointerventional procedure, and (3) identify knowledge gaps and discuss future research directions.